Síndrome celíaco. Presentación de un caso por intolerancia al gluten. - Borbolla Vacher, Liane; de la Cámara, Carlos M.; Cárdenas Valdés, René F.; Corral Almonte, José F. (Revista Cubana de Pediatría, 2023)
Presentación de un caso.